Ecopolitics Podcast, Episode 9: Ecofeminism and Queer Ecology - Katz-Rosene, Ryan; Andrée, Peter (Université d'Ottawa | University of Ottawa, 2020)
Dr. Catriona Sandilands and Dr. Sherilyn McGregor share with us the ways in which ecofeminism, and queer ecology, serve to diversify and deepen how we look at the policies and day-to-day practices of environmental politics. [Produced by Nicole Bedford; Artwork by Adam Gibbard; Transcription by Allison Brown; Additional Resources prepared by Ashley Fearnall].